2015
DOI: 10.23971/jefl.v3i2.65
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers’ Reading Habits and Preferences

Abstract: This study investigates the reading habit and preferences of the Student Teachers studying in their first year at the graduate school in Malang. Although with the advance of technology, media and many factors influencing reading habits and their preferences, the subjects of the study still have good reading habit and positive attitude towards reading activities. To collect the data, the researcher employs the questionnaire with 40 items adapted from a similar research. The items were designed for evaluating re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Hence by providing a variety of topics for reading and a conducive place to read, such as a mini-library at home, reading habits can be increased among students. Moreover, learners' reading habits can be increased by providing a variety of reading materials such as books, magazines, newspapers, graphic novels, comic books, fiction or non-fiction texts and many more (Priajana, 2013). In order to compete in the global marketplaces of the future, young generations, particularly students, need to develop good reading habits.…”
Section: Reading Habitmentioning
confidence: 99%
“…Hence by providing a variety of topics for reading and a conducive place to read, such as a mini-library at home, reading habits can be increased among students. Moreover, learners' reading habits can be increased by providing a variety of reading materials such as books, magazines, newspapers, graphic novels, comic books, fiction or non-fiction texts and many more (Priajana, 2013). In order to compete in the global marketplaces of the future, young generations, particularly students, need to develop good reading habits.…”
Section: Reading Habitmentioning
confidence: 99%
“…Moreover, with the development of technology and media, those teachers who do not read books habitually spend either less time on reading or do not read at all. In this technology era, teachers mostly prefer to spend their free time by watching movies online, listening to music, and social networks such as Facebook, Tik-tok, Instagram and Twitter (Priajana, 2015).…”
Section: What Is An E-book?mentioning
confidence: 99%
“…Iftani (2015) conducted a study on EFL college students in East Java, the findings indicated that most of the respondents read for some purposes, such as for pleasure, assignments, knowledge and examination purpose. In a study conducted by Priajana (2013), EFL students mostly read topics that is related to their academic purpose regardless of reading for pleasure. So, many observations reveal that students read mainly for examination purpose rather than for other purposes.…”
Section: Purpose Of Readingmentioning
confidence: 99%